Redes sociales como instrumento de marketing deportivo. Caso Santa Rita de Vinces temporada 2019 - Palma Bajaña, Melissa Michelle (2020)
Analyzing social networks as a sports marketing tool gave us the opportunity to get to know the reality of the Santa Rita Club in depth. Institution that tries to adapt to new forms of communication and that in this way has made mistakes that have not made it possible to meet the objectives set: To grow its name as a brand, attract the public and attract sponsors. Through an interview with the club's public relations officer, truthful information was obtained and through surveys it was possible to know the impact that social networks have on the Vinceño club. Using Facebook, Instagram and Twitter, club information is disseminated; it was known that sports marketing have been focused on Facebook. But, the contents do not fully impact users causing confusion in aspects such as representative colors, stadium and tournament in which the team competes, in addition, strategies have not been implemented that make the club's name grow as an attractive product for the hobby. Given the situation already described, it is recommended to open up professionals in the area, analyze the objectives and considers a restructuring that allows them to improve content, grow as an institution and generate economic income from attending stadiums or possible contracts with sponsors.